2009
DOI: 10.1016/j.biomaterials.2008.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical properties of individual, electrospun fibrinogen fibers

Abstract: We used a combined atomic force microscopic (AFM)/fluorescence microscopic technique to study the mechanical properties of individual, electrospun fibrinogen fibers in aqueous buffer. Fibers (average diameter 208 nm) were suspended over 12 μm-wide grooves in a striated, transparent substrate. The AFM, situated above the sample, was used to laterally stretch the fibers and to measure the applied force. The fluorescence microscope, situated below the sample, was used to visualize the stretching process. The fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 25 publications
3
91
0
Order By: Relevance
“…Similarities were observed in the extensibilities of the individual fibers and the mats. However, both the peak stress and the modulus of elasticity of the mats were approximately an order of magnitude lower than the single fibers, suggesting that amongst other factors, the mechanical properties of the mats are a complex combination of the mechanical properties of the individual fibers making up the mats [103].…”
Section: Electrospinning Fibrinogenmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarities were observed in the extensibilities of the individual fibers and the mats. However, both the peak stress and the modulus of elasticity of the mats were approximately an order of magnitude lower than the single fibers, suggesting that amongst other factors, the mechanical properties of the mats are a complex combination of the mechanical properties of the individual fibers making up the mats [103].…”
Section: Electrospinning Fibrinogenmentioning
confidence: 96%
“…As such, it was demonstrated that scaffold remodeling and collagen matrix production were inversely related to the aprotinin concentration, with nearly complete remodeling taking place after 14 days in even the highest aprotinin concentrations (Figure 7). The mechanical properties of individual, electrospun fibrinogen fibers have been evaluated [103] and compared to the mechanical properties of wet, non-woven mats made from randomly oriented electrospun fibrinogen fibers [104]. Similarities were observed in the extensibilities of the individual fibers and the mats.…”
Section: Electrospinning Fibrinogenmentioning
confidence: 99%
“…Recently, a method using an atomic force microscope (AFM) has been described that allows tensile testing of individual nanofibres to high strains with sub nN force resolution. 20,21 The method is applicable to soft, elastomeric materials and allows the samples to be immersed in a fluid. The technique is ideally suited for actuation testing of individual hydrogel nanofibres.…”
Section: 10mentioning
confidence: 99%
“…The fibres were stretched by lateral movement of the fully-immersed AFM cantilever, using the method similar to that described previously 20,21 and illustrated in Fig. 1a.…”
Section: Actuation Measurementsmentioning
confidence: 99%
“…45 Carlisle et al analyzed the mechanical properties of a single electrospun Fbg nanofiber, using a combined atomic force/fluorescence microscopic technique, and the result indicated that Fbg nanofiber had a high extensibility. 46 High-extensibility fiber scaffolds have been found to be more widely applicable for in vitro and in vivo tissue engineering due to their flexibility. Electrospun Fbg nanofibers that Abbreviations: Fbg, fibrinogen; SEM, scanning electron microscope.…”
Section: Fbg and Fbn Micro/nanofiber As Scaffoldsmentioning
confidence: 99%